State Responsibility in Implementing Bandung City Regional Regulation Number 24 of 2012 concerning the Implementation and Handling of Social Welfare from the Siyasah Maliyah Perspective - Dewi Sulastri; Listyani Effendi; M Yahya Wahyudin; Abu Sanmas (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Philanthropic funds have the potential to address welfare disparities in society. Fund collection mechanisms have evolved alongside technological advancements. The Bandung City Social Welfare Office issued a policy on the management of money or goods through Bandung City Regional Regulation Number 24 of 2012 concerning the Organization and Handling of Social Welfare. This study will examine the implementation that occurs in society engaging in fundraising activities. This research is qualitative and falls under empirical juridical research. The approach used is statutory with a descriptive method. Data for the study are sourced from observations, interviews, and literature studies of legislation, books, journals, and other documents. The findings of this research are as follows: First, there is a gap between existing legal regulations and practices in the field, especially regarding supervision of the implementation of fundraising activities. Second, the impact of the Bandung City Social Welfare Office's performance and the implementation of fundraising activities in general can improve the welfare index, but there are still many areas that need improvement. Third, Bandung City Regional Regulation Number 24 of 2012 was created as a form of state responsibility (mas’uliyyah ad-daulah). The Bandung City Government provides social guarantees in two forms. First, providing ample opportunities for productive activities and providing direct cash assistance.